2012
DOI: 10.1002/chem.201103227
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Optical Properties of Diaza‐ and Tetraazatetracenes

Abstract: A series of functionalized diaza- and tetraazatetracenes was synthesized, either by condensation of an aromatic diamine with an ortho-quinone/diethyloxalate followed by chlorination with POCl(3) to give diazatetracenes or by palladium-catalyzed coupling of a phenylenediamine with various 2,3-dichloroquinoxalines to give tetraazatetracenes (after oxidation with MnO(2)). Representative examples included halogenated and nitrated derivatives. The optical properties of these azatetracenes were discussed with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 38 publications
1
43
0
2
Order By: Relevance
“…f, 8c, 9 Recently, Bunz et al. found that N‐heteroacenes are resistive to degradation (oxidation or dimerization) as compared to their parent oligoacenes 6a. b, d More importantly, it has been shown that the number, position, and valence states of N atoms in frameworks contribute significantly to the physical properties of N‐substituted PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…f, 8c, 9 Recently, Bunz et al. found that N‐heteroacenes are resistive to degradation (oxidation or dimerization) as compared to their parent oligoacenes 6a. b, d More importantly, it has been shown that the number, position, and valence states of N atoms in frameworks contribute significantly to the physical properties of N‐substituted PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is observed in solutions, where 2a exhibits a deep colour in daylight and strong yellow-orange emission under illumination at 365 nm, while 1a and 3a are less strongly fluorescent ( Figure 1). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Figure 2 shows the absorption spectra of compounds 1a-3a, compared with those of the Nheteroacenes 1b-3b 14,17,18 in hexane. The diazaiptycenes showed similar curves compared to the diazaacenes, indicating that there is no significant electronic coupling between the two isolated benzene rings and the azaacene-unit.…”
Section: Resultsmentioning
confidence: 98%
“…It is essential to lower the LUMO energy level of azatetracenes to achieve better n‐type performance. From the synthetic perspective, the introduction of electron‐withdrawing units could evidently deepen the LUMO of azatetracenes . Mark et al.…”
Section: Methodsmentioning
confidence: 99%